Experimental and Theoretical Soft X‐Ray Absorption Study on Co3+ Ion Spin States in Sr2−xCaxCoO3F. Issue 8 (21st May 2018) - Chin, Yi‐Ying; Hu, Zhiwei; Su, Yu; Tsujimoto, Yoshihiro; Tanaka, Arata; Chen, Chien‐Te
Abstract : To investigate the influence of chemical pressure on the eg orbital occupation and the spin state of Co 3+ ions, which are closely related to electrochemical reaction of catalysts for energy storage applications, we have prepared a new material Sr1.7 Ca0.3 CoO3 F, which was previously predicted to possess an intermediate‐spin (IS) state with eg 1 configuration. Our experimental Co‐ L 2, 3 X‐ray absorption spectrum of Sr1.7 Ca0.3 CoO3 F was very similar to those of the high‐spin (HS) Co 3+ references Sr2 CoO3 F and Sr2 CoO3 Cl indicating an HS Co 3+ ground state. The HS‐Co 3+ ground state in Sr1.7 Ca0.3 CoO3 F was further confirmed by using O‐ K XAS spectra and theoretical simulation of the Co‐ L 2, 3 XAS spectra with configuration‐interaction cluster calculations. We present theoretical energy diagrams of three spin states for Co 3+ ions in Sr2 CoO3 F as a function of external pressure based on the crystal structures observed in a previous high‐pressure study. We have also investigated the structural conditions that are required to stabilize the IS state in this effective local pyramidal structure theoretically, and found that the in‐plane Co–O distance (<1.88 Å) and the out‐of‐plane Co displacement (<0.18 Å) are critical conditions for obtaining the IS‐Co 3+ ground state. Abstract : The X‐ray absorption spectra at the Co‐ L 2, 3 edges and the O‐ K edge of Sr1.7 Ca0.3 CoO3 F are different from those of EuCoO3 with low‐spin Co 3+, but similar to those of Sr2 CoO3 F and Sr2 CoO3 Cl with high‐spin Co 3+ . This indicates that Co ions in Sr1.7 Ca0.3 CoO3 F have a high‐spin‐Co 3+ state further confirmed by theoretical simulation. These results contradict the intermediate spin state predicated previously.